2014
DOI: 10.1016/j.jtcvs.2012.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Simple interrupted suturing increases valve performance after aortic valve replacement with a small supra-annular bioprosthesis

Abstract: Simple interrupted sutures provide larger effective orifice areas and reduce the incidence of prosthesis-patient mismatch after aortic valve replacement with a small supra-annular bioprosthesis. This suture technique is preferred in those patients to maximize valve performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 15 publications
7
50
1
1
Order By: Relevance
“…We previously demonstrated in a similar study that the use or nonuse of subannular pledgets did not influence valve hemodynamic performance. 17 Recent work by Tabata and colleagues 21 has supported that an interrupted nonpledget technique may be associated with a lower incidence of patient-prosthesis mismatch due to a relatively larger increase in effective orifice area. Therefore, the importance of this factor should be assessed in further work.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated in a similar study that the use or nonuse of subannular pledgets did not influence valve hemodynamic performance. 17 Recent work by Tabata and colleagues 21 has supported that an interrupted nonpledget technique may be associated with a lower incidence of patient-prosthesis mismatch due to a relatively larger increase in effective orifice area. Therefore, the importance of this factor should be assessed in further work.…”
Section: Discussionmentioning
confidence: 99%
“…An explain of the discrepancy with our results might be found in fact that the patients in the study were not randomized and it might be possible that the initial tissue gathered underneath the valve may remodel over time and that the initial obstruction may decrease. In this regard, the data from Tabata et al showed a trend in this direction (4).…”
Section: Potential Mechanisms Of Flow Obstruction In the Msp Techniquementioning
confidence: 93%
“…In this regard, two recent studies (4,5) involving small bioprostheses, i.e. with labeled sizes of 19 mm and 21 mm, came to different conclusions.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
See 1 more Smart Citation
“…Our profession recognizes the presence of, and indeed the need for, multiple approaches to the care of a patient. Faced with an open aortic valve replacement, the surgeon must balance a triad of issues: (1) to maximize the effective orifice area (EOA) of the biologic prosthetic aortic valve (in part by not reducing the size of the annulus by the surgical technique of implantation), (2) to minimize the risk of a paravalvular leak, and (3) to optimize the ease of implantation.…”
mentioning
confidence: 99%